2007
DOI: 10.1038/sj.pcan.4501022
|View full text |Cite
|
Sign up to set email alerts
|

Association between prostate-specific antigen and leptin, adiponectin, HbA1c or C-peptide among African-American and Caucasian men

Abstract: Prior studies report slightly lower prostate-specific antigen (PSA) levels among obese men. To understand this effect, we investigated the association between PSA and blood HbA1c, C-peptide, leptin and adiponectin levels in African-American (AA) (n ¼ 121) and Caucasian (CA) (n ¼ 121) men. Among AA men, PSA levels decreased with increasing C-peptide levels (PSA ¼ 0.99, 0.93, 0.75 and 0.53 ng ml À1 across quartiles of C-peptide, respectively; P trend ¼ 0.005). Among CA men, PSA levels decreased with increasing H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 55 publications
2
38
1
Order By: Relevance
“…As our study was the first to investigate the diabetic medication in detail, we could further show the largest reduction for men using insulin, whereas oral diabetic medication was associated with a lower PSA reduction and whereas diabetic men with no medication tended to have similar PSA levels compared with nondiabetic men. The hypothesis that more severe forms of diabetes might be associated with a lower PSA level was further supported by the inverse association of HbA1c measurements with PSA levels in our study, a result that was also seen by Fowke et al (18) in Caucasian men. In contrast, Fukui et al (16) found no association between PSA levels and either Hba1c or medication in Japanese men.…”
Section: Discussionsupporting
confidence: 78%
“…As our study was the first to investigate the diabetic medication in detail, we could further show the largest reduction for men using insulin, whereas oral diabetic medication was associated with a lower PSA reduction and whereas diabetic men with no medication tended to have similar PSA levels compared with nondiabetic men. The hypothesis that more severe forms of diabetes might be associated with a lower PSA level was further supported by the inverse association of HbA1c measurements with PSA levels in our study, a result that was also seen by Fowke et al (18) in Caucasian men. In contrast, Fukui et al (16) found no association between PSA levels and either Hba1c or medication in Japanese men.…”
Section: Discussionsupporting
confidence: 78%
“…6 In a cross-sectional sample of the Southern Community Cohort Study aged 40-78 years, Fowke et al reported decreasing mean PSA with increasing HbA1c quartiles (p trend =0.005) among Caucasian men. 7 In contrast to these cross-sectional studies and our current report, longitudinal observations in a Japanese hospital cohort found increases in HbA1c and PSA to be concordant (5.7% increase per 1-unit HbA1c change, p<0.001). 27 However, when the data were analyzed in a cross-sectional manner, the authors reported small non-significant inverse relationships between HbA1c and PSA.…”
Section: Discussioncontrasting
confidence: 51%
“…Specifically, previous studies have demonstrated lower PSA in men with type 2 diabetes mellitus (T2DM) and inverse associations between poor glycemic control, as assessed by hemoglobin A1c (HbA1c), and PSA. [6][7][8][9] There are several possible explanations why PSA may be lower among men with T2DM than among men without T2DM, including greater obesity and more frequent use of medications used to treat dyslipidemia and hypertension. Men with higher BMI have lower mean total PSA than men with lower BMIs, [10][11][12] possibly due to hemodilution from increased plasma volume in larger men, 13 or lower androgen levels that characterize more obese and insulin resistant adult males.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies reported that men with MS had lower PSA than men without MS. [1][2][3][4] Data from the National Health and Nutrition Examination Survey in [2001][2002][2003][2004] showed that the mean PSA of men with MS is slightly lower than of men without MS (0.98 ng/mL vs 0.87 ng/mL), although it was not statistical significant (P = 0.20).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the previous studies that examined the relationship of MS and PSA did not adjust prostate volume. [1][2][3][4][5][6] Interestingly, the PSA of men with MS was not higher than that without MS in those studies. mass (serum PSA 9 plasma volume) was used to adjust the plasma volume, and there were no significant differences of PSA mass between men with MS and without MS.…”
Section: Introductionmentioning
confidence: 92%